Polymers for high temperature resistant salt water based fracturing fluid thickeners for oil and gas wells
By introducing hyperbranched polyether side groups on the molecular chain of the thickener of the oil and gas wells, polymers for thickener with high temperature brine-based fracturing liquid are designed, which solves the problem of thickener performance attenuation caused by high formation temperature and high mineralization water, and achieves the temperature, salt resistance and rapid dissolution effects of the thickener, which is suitable for the fracturing process in deep wells in oil fields.
Patent Information
- Application Number
- CN202210839560.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-07-15
AI Technical Summary
During the development of oil and gas fields, the high temperature of high temperature well formations and high mineralization water leads to a significant decrease in the viscosity of the fracturing liquid thickener and the ability to carry and suspend sand, affecting the production increase effect and oil production cost.
A polymer for thickening agent for high-temperature brine-based fracturing liquid with oil and gas wells was developed. By introducing a macromolecular polyether side group with a hyperbranched structure on the thickener molecular chain, the general formula of the copolymer structure is designed as follows Formula I, and a specific preparation method is adopted, including dissolving monomers, heating polymerization, adding hydrolysis neutralizing agents, etc., to prepare a thickening agent with temperature resistance, salt resistance and fast dissolution speed.
The stable performance of the thickener in high temperature and high salt environment is achieved, good viscosity and suspension ability is maintained, and it is suitable for the continuous fracturing process of deep wells in oil fields, reducing oil production costs.
Smart Images

Figure BDA0003749414010000011 
Figure BDA0003749414010000021 
Figure BDA0003749414010000041
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a polymer used as a thickener for high temperature resistant salt water-based fracturing fluid in oil and gas wells which is heat-resistant, salt-resistant and fast dissolving, and also relates to a preparation method of the thickener, belonging to the technical field of fracturing fluid for developing low permeability reservoirs in oil and gas fields. Background Art
[0002] In the middle and late stages of oil and gas field development, the depth of oil wells continues to increase, and the formation temperature of some high-temperature wells approaches or exceeds 200°C, which brings difficulties to unconventional technologies such as hydraulic fracturing. At the same time, the mineralization of deep well formation water is high. After interacting with the anions of the side chains of the thickener polymer molecules, the rigidly stretched polymer molecular chains curl and collapse, resulting in a significant attenuation of the viscosity, sand carrying and sand suspension capacity of the thickener polymer used for fracturing, a decrease in the production increase effect, and a significant increase in oil production costs. In addition, with the increasing number of shale gas, sandstone gas and other oil and gas wells and the rapid development of offshore oil fields, the proportion of unconventional oil production technologies such as hydraulic fracturing is increasing. The high-performance fracturing fluid prepared by directly mixing the thickener with the high-mineralization water returned from the oil and gas wells or the seawater taken locally is conducive to saving a large amount of fresh water resources, improving efficiency, and achieving the purpose of increasing oil and gas production and efficiency. Therefore, it is necessary to develop a thickener polymer that has both temperature resistance and salt resistance and a fast dissolution rate. Summary of the invention
[0003] In order to solve the above technical problems, the present invention proposes a polymer for thickening agent and a preparation method thereof, specifically a polymer for thickening agent of high temperature resistant salt water-based fracturing fluid for oil and gas wells.
[0004] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:
[0005] A polymer for a high temperature resistant salt water based fracturing fluid thickener for oil and gas wells, wherein the general structural formula of the copolymer is as follows:
[0006]
[0007] The structural formula of Q is as follows:
[0008]
[0009] a, b, c, d are positive integers and a:b:c:d=45-70:17-35:7-15:5-10, and the viscosity average molecular weight of the PAM copolymer is 2.0×10 7 -3.8×10 7 g / mol.
[0010] The preparation method of a polymer for a high temperature resistant salt water based fracturing fluid thickener for oil and gas wells comprises the following steps:
[0011] S1: dissolving acrylamide (AM), acrylic acid (AA), 2-acrylamido-2-methylpropyl sulfonic acid (AMPS), and acrylic acid monohyperbranched polyether alcohol ester (AHPEA) in deionized water at a mass ratio of 46.5-64:17.5-28:7-15:10-20 to prepare a reaction solution,
[0012] S2: then heating to 50-85° C. under nitrogen protection, adding an aqueous solution of a redox initiator and an aqueous solution of a water-soluble azo initiator to the reaction solution prepared in S1 at a constant rate, and reacting for 3-8 hours to perform a polymerization reaction, wherein the addition amount of the redox initiator and the water-soluble azo initiator is 0.15-0.45% of the mass of acrylamide (AM), respectively;
[0013] S3: Then, a hydrolysis neutralizing agent is added to step S2 to adjust the pH value of the system to 7.0-7.3, and then the PAM copolymer powder is obtained after precipitation, freeze drying, crushing and sieving.
[0014] Preferably, the redox initiator is at least one of a persulfate or a sulfite; wherein the persulfate is at least one of ammonium persulfate and potassium persulfate, and the sulfite is at least one of sodium sulfite and sodium bisulfite.
[0015] Preferably, the water-soluble azo initiator is at least one of azobiscyanovaleric acid, azobisisobutylimidazoline hydrochloride and azobisisopropylimidazoline.
[0016] Preferably, the mass percentage concentration of the aqueous solution of the redox initiator and the aqueous solution of the water-soluble azo initiator is both 5%.
[0017] Preferably, the hydrolysis neutralizing agent is sodium hydroxide.
[0018] Preferably, the particle size of the PAM copolymer after crushing and grinding is not less than 120 mesh standard sieve, and the water content is not more than 1.5%.
[0019] The present invention aims at the research difficulties of a fracturing fluid thickener with high temperature resistance, high salt resistance and high dissolution rate. By structural design, a macromolecular polyether side group with a hyperbranched structure is introduced into the thickener molecular chain, thereby meeting the requirements of high temperature resistance, high salt resistance and high dissolution rate. The thickener suspension prepared by the thickener is suitable for the needs of continuous preparation of fracturing operations.
[0020] Compared with the prior art, the invention is beneficial in that the copolymer for thickener of the invention has the advantages of temperature resistance, salt resistance, fast dissolution rate, etc., and is suitable for the continuous fracturing process of deep wells in oil fields.
[0021] 1) Compared with linear polyethylene glycol, the molecular structure of hyperbranched polyether is irregular, and it is not easy to fold the molecular chain in an orderly manner at high temperature, and it always maintains good hydrophilicity, which will not cause the molecular chain to curl and the viscosity of the system to decrease. Therefore, the hyperbranched polyether molecular structure gives the thickener (PAM copolymer) aqueous solution excellent temperature resistance; 2) The hyperbranched polyether molecule is a non-ionic water-soluble polymer with poor sensitivity to positive and negative ions (does not chemically react with positive and negative ions), so the PAM copolymer itself has good salt resistance; further, the three-dimensional hyperbranched polyether macromolecule covers or wraps around the anionic groups in the PAM molecular chain, which has a protective effect on anions such as carboxylate and sulfonate, reducing their chances of interacting with high-valent cations, so the hyperbranched polyether gives the thickener (PAM copolymer) aqueous solution excellent salt resistance; 3) AHPEA monomer randomly introduces the hyperbranched polyether structure into the PAM copolymer molecular chain, and the three-dimensional structure of the water The soluble hyperbranched polyether makes the arrangement of the copolymer molecular chains relatively loose, which is conducive to the diffusion and hydration of water molecules. Therefore, the PAM copolymer dissolves quickly in water, meeting the needs of on-site continuous fracturing construction; 4) The hyperbranched polyether has a certain hygroscopic property, which is easy to conduct and eliminate the static electricity between the molecular chains, which is conducive to grinding the PAM copolymer into a finer powder; 5) The heat-resistant, salt-resistant, and fast-dissolving thickener of the present invention has a simple synthesis process and mild reaction conditions, and the obtained product has a large molecular weight, a high viscosity of the aqueous solution, and good performance; 6) When the PAM copolymer needs to be degraded into small molecules after completing the fracturing task, the three-dimensional hyperbranched polyether molecular chains do not entangle and have a very low viscosity. This part is not easy to be adsorbed on the well surface, which is conducive to the backflow of the degradation liquid. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the infrared spectrum of the PAM copolymer synthesized in Example 1 of the present invention.
[0023] Figure 2 This is the infrared spectrum of the PAM copolymer synthesized in Example 4 of the present invention.
[0024] Figure 3 This is a graph showing the temperature resistance test results of the PAM copolymer synthesized in the present invention.
[0025] Figure 4 The graph is a relationship curve between the concentration and viscosity of the PAM copolymer solution synthesized in the present invention. DETAILED DESCRIPTION
[0026] The present invention will be described in more detail below, wherein preferred embodiments of the present invention are shown, and the acrylic acid monohyperbranched polyether alcohol ester (AHPEA) used is prepared according to the following method and applied in preferred embodiments, wherein the hydroxy polyether is synthesized using citric acid as a starter according to the disclosure of the document ACS Macro Lett. 2017, 6, 35-40, and the average molecular weight of the synthesized hydroxy polyether is 1.0×10 3 -8×10 3 g / mol, and the molecular weight distribution is in the range of 1.5-3.0.
[0027] The structural formula of hydroxy polyether is as follows:
[0028]
[0029] The synthesis method of acrylic acid monohyperbranched polyether alcohol ester (AHPEA) comprises the following steps:
[0030] 1) Place the hydroxy polyether in a round-bottom flask and heat it to 100°C. Pump down the air for 2 hours under vacuum conditions (not higher than -0.1 MPa).
[0031] 2) After cooling to 0°C with an ice-water bath, add triethylamine in an amount equal to the molar number of acryloyl chloride, and stir evenly with a magnetic stirrer. Then, gradually drop acryloyl chloride in an amount of 1 / 10-1 / 5 of the molar number of the hydroxy polyether, control the dropwise addition time to 30-60 minutes, and react at room temperature for 24 hours.
[0032] 3) After diluting with 5 times the mass of anhydrous methanol, precipitating in ice-cold anhydrous ether, centrifuging, and collecting the oily substance, which is the target product, acrylic acid monohyperbranched polyether alcohol ester (AHPEA).
[0033] It should be understood that those skilled in the art can modify the invention described herein and still achieve the beneficial effects of the invention. Therefore, the following description should be understood as being widely known to those skilled in the art, and not as a limitation of the present invention.
[0034] Example 1
[0035] A polymer for a thickener that is heat-resistant, salt-resistant, and fast-dissolving and a preparation method thereof, the preparation method comprising the following steps:
[0036] S1. Add 180 parts of deionized water into a reactor, then add 46.5 parts of AM, 17.5 parts of AA, 15 parts of AMPS and 20 parts of AHPEA, and dissolve the raw materials in deionized water under stirring;
[0037] S2. High-purity nitrogen was continuously introduced into the reactor, and the aqueous solution of the monomer was heated to 50°C. 0.07 parts of ammonium persulfate and 0.03 parts of sodium sulfite (mixed to prepare a 5% aqueous solution by mass) were added dropwise at a uniform rate for 3.0 hours and 0.1 parts of azobiscyanovaleric acid (prepared to prepare a 5% aqueous solution by mass) for 4.0 hours, respectively. The reaction was maintained at 50°C and in a nitrogen atmosphere for a total of 8 hours.
[0038] S3. After the reaction is completed, the thickener PAM copolymer powder is obtained after hydrolysis, precipitation, freeze drying, crushing and sieving. The molecular weight of the copolymer is 2.0×10 7 g / mol.
[0039] Example 2
[0040] A polymer for a thickener that is heat-resistant, salt-resistant, and fast-dissolving and a preparation method thereof, the preparation method comprising the following steps:
[0041] S1. Add 250 parts of deionized water into the reactor, then add 64 parts of AM, 28 parts of AA, 7 parts of AMPS and 20 parts of AHPEA, stir to dissolve the raw materials;
[0042] S2. High-purity nitrogen was continuously introduced into the reactor, and the aqueous solution of the monomer was heated to 80°C. 0.1 part of ammonium persulfate and 0.1 part of sodium bisulfite (mixed to prepare a 5% aqueous solution) were uniformly added dropwise for 2.0 hours and 0.2 part of azodiisopropylimidazoline (prepared to prepare a 5% aqueous solution) for 4.0 hours, respectively. The temperature was maintained at 80°C and the nitrogen atmosphere was maintained for a total reaction of 8 hours.
[0043] S3. After the reaction is completed, the thickener PAM copolymer powder is obtained after hydrolysis, precipitation, freeze drying, crushing and sieving. The molecular weight of the powder is 3.8×10 7 g / mol.
[0044] Example 3
[0045] A polymer for a thickener that is heat-resistant, salt-resistant, and fast-dissolving and a preparation method thereof, the preparation method comprising the following steps:
[0046] S1. Add 200 parts of deionized water into the reactor, then add 56 parts of AM, 28 parts of AA, 10 parts of AMPS and 10 parts of AHPEA, stir to dissolve the raw materials;
[0047] S2. High-purity nitrogen was continuously introduced into the reactor, and the aqueous solution of the monomer was heated to 70°C. 0.1 part of potassium persulfate, 0.1 part of sodium sulfite (mixed to prepare a 5% aqueous solution by mass) and 0.1 part of azobisisobutylimidazoline hydrochloride (prepared to prepare a 5% aqueous solution by mass) were added dropwise at a uniform rate for 2.0 hours, respectively. The temperature was maintained at 70°C and the nitrogen atmosphere was maintained for a total reaction of 3.0 hours.
[0048] S3. After the reaction is completed, the thickener PAM copolymer powder is obtained after hydrolysis, precipitation, freeze drying, crushing and sieving. The molecular weight of the copolymer is 2.37×10 7 g / mol.
[0049] Example 4
[0050] A polymer for a thickener that is heat-resistant, salt-resistant, and fast-dissolving and a preparation method thereof, the preparation method comprising the following steps:
[0051] S1. Add 190 parts of deionized water into the reactor, then add 52.5 parts of AM, 17.5 parts of AA, 7 parts of AMPS and 15 parts of AHPEA, stir to dissolve the raw materials;
[0052] S2. High-purity nitrogen was continuously introduced into the reactor, and the aqueous solution of the monomer was heated to 65°C. 0.10 parts of ammonium persulfate and 0.06 parts of sodium sulfite aqueous solution (mixed to prepare an aqueous solution with a mass concentration of 5%) were added dropwise at a uniform rate for 2.0 hours and 0.1 parts of azobisisobutylimidazoline hydrochloride and 0.05 parts of azobiscyanovaleric acid aqueous solution (mass concentration of 5%) were added dropwise for 3.0 hours, and the reaction was carried out for a total of 5.0 hours while maintaining 65°C and a nitrogen atmosphere;
[0053] S3. After the reaction is completed, the thickener PAM copolymer powder is obtained after hydrolysis, precipitation, freeze drying, crushing and sieving. The molecular weight of the copolymer is 3.15×10 7 g / mol.
[0054] Example 5
[0055] A polymer for a thickener that is heat-resistant, salt-resistant, and fast-dissolving and a preparation method thereof, the preparation method comprising the following steps:
[0056] S1. Add 240 parts of deionized water into the reactor, then add 60 parts of AM, 20 parts of AA, 15 parts of AMPS and 15 parts of AHPEA, stir to dissolve the raw materials;
[0057] S2. High-purity nitrogen was continuously introduced into the reactor, and the aqueous solution of the monomer was heated to 75°C. 0.12 parts of ammonium persulfate and 0.08 parts of sodium sulfite aqueous solution (mixed to prepare an aqueous solution with a mass concentration of 5%) were added dropwise at a uniform rate for 2.5 hours, and 0.08 parts of azobisisopropylimidazoline hydrochloride and 0.06 parts of azobiscyanovaleric acid aqueous solution (mass concentration of 5%) were added dropwise for 4.0 hours, and the temperature was maintained at 75°C and the nitrogen atmosphere was maintained for a total reaction of 6.0 hours.
[0058] S3. After the reaction is completed, the thickener PAM copolymer powder is obtained after hydrolysis, precipitation, freeze drying, crushing and sieving. The molecular weight of the copolymer is 3.59×10 7 g / mol.
[0059] Example 6
[0060] A polymer for a thickener that is heat-resistant, salt-resistant, and fast-dissolving and a preparation method thereof, the preparation method comprising the following steps:
[0061] S1. Add 225 parts of deionized water into the reactor, then add 48 parts of AM, 24 parts of AA, 15 parts of AMPS and 20 parts of AHPEA, stir to dissolve the raw materials;
[0062] S2. High-purity nitrogen was continuously introduced into the reactor, and the aqueous solution of the monomer was heated to 65°C. 0.10 parts of potassium persulfate and 0.06 parts of sodium bisulfite aqueous solution (mixed to prepare an aqueous solution with a mass concentration of 5%) were added dropwise at a uniform rate for 2.5 hours and 0.1 parts of azobisisobutylimidazoline hydrochloride and 0.06 parts of azobiscyanovaleric acid aqueous solution (mass concentration of 5%) were added dropwise for 4.0 hours, and the temperature was maintained at 65°C and the nitrogen atmosphere was maintained for a total reaction of 7.0 hours.
[0063] S3. After the reaction is completed, the thickener PAM copolymer powder is obtained after hydrolysis, precipitation, freeze drying, crushing and sieving. The molecular weight of the copolymer is 2.9×10 7 g / mol.
[0064] It should be noted that the reactants in the above preferred embodiments are added to participate in the reaction according to mass fractions.
[0065] Thickener structure characterization
[0066] The thickener PAM copolymer product obtained in Example 1 was characterized by Fourier transform infrared spectroscopy. Figure 1 shown. Figure 1 Display: Product at 3191~3507cm -1 A broad absorption peak appears at 1118 cm -1The absorption peak at is attributed to the absorption peak of the ether bond (-O-) in the product structure, indicating that the thickener PAM copolymer was synthesized in Example 1.
[0067] The thickener PAM copolymer product obtained in Example 4 was characterized by Fourier transform infrared spectroscopy. Figure 2 shown. Figure 2 Display: Product at 3185~3462cm -1 A broad absorption peak appears at 1121 cm -1 The absorption peak at is attributed to the absorption peak of the ether bond (-O-) in the product structure, indicating that the thickener PAM copolymer was synthesized in Example 4.
[0068] Thickener Performance Test
[0069] (1) Thickener temperature and salt resistance test
[0070] The products of Example 1 (20 parts), Example 3 (10 parts) and Example 4 (15 parts) with different AHPEA contents were selected as test samples, and a copolymer of acrylamide and sodium acrylate (the mass ratio of the two monomers was about 3:1) used as a thickener on the market was selected as a comparative sample (its viscosity average molecular weight was 2.52×10 7 The thickener solution with a mass fraction of 0.5% was prepared with seawater from the Yellow Sea and measured using an RS6000 Haake rheometer at a shear rate of 170 s -1 Under the condition of , the solution is heated from 80℃ to 200℃, and the test results are as follows Figure 3 shown.
[0071] Figure 3 The test results show that: in the test temperature range of 80-200°C, the viscosity of Example 1, Example 3 and Example 4 is higher than that of the control sample, and has significant temperature and salt resistance. Moreover, the viscosity reduction rates of the four sample solutions of Example 1, Example 3, Example 4 and the control sample from 80°C to 200°C are 39.7%, 42.8%, 40.1% and 60.3% respectively, indicating that the introduction of the thickener copolymer can effectively improve the temperature resistance of the thickener solution.
[0072] (2) Effect of thickener concentration on viscosity
[0073] The samples synthesized in Example 1, Example 3 and Example 4 were prepared with different concentrations of thickener solutions using return water from the oil field (Huanghekou Oilfield). The RS6000 Haake rheometer was used to measure the viscosity of the samples at 170s. -1 and the viscosity of the thickener solution at 160°C. Figure 4 shown.
[0074] Figure 4 The test results show that the flowback aqueous solutions of the tested samples Example 1, Example 3 and Example 4 all exhibit high apparent viscosity at different mass concentrations, and as the mass concentration fraction of the thickener polymer increases, the viscosity of the solution increases rapidly.
[0075] (3) Solubility test of thickener
[0076] Example 1, Example 3, Example 4 and the comparative sample were prepared with seawater and oilfield return water to prepare a solution with a mass concentration of 0.3%, and stirred at 6000 rpm with a high-speed stirrer for 2 min, 5 min and 10 min respectively. Then, the RS6000 rheometer was used to measure the rheological properties at 170 s. -1 The viscosity of the solution obtained under the conditions of 3 times and room temperature (average value is taken), the results are shown in Table 1 and Table 2.
[0077] Table 1. Viscosity of four samples of seawater solutions
[0078] <![CDATA[η 2min (cps)]]> <![CDATA[η 5min (cps)]]> <![CDATA[η 10min (cps)]]> <![CDATA[η 2min / or 10min ]]> Example 1 87±0.1 99±2.5 102±3.1 85.3% Example 3 65±2.7 84±1.0 86±0.6 75.6% Example 4 81±1.3 90±5.6 96±4.4 84.4% Comparison sample 35±1.2 51±0.9 57±6.7 61.4%
[0079] Table 2. Viscosity of the four sample flowback water solutions
[0080] <![CDATA[η 2min (cps)]]> <![CDATA[η 5min (cps)]]> <![CDATA[η 10min (cps)]]> <![CDATA[η 2min / or 10min ]]> Example 1 85±1.3 97±3.6 101±0.7 84.2% Example 3 67±0.8 81±4.8 84±2.9 79.8% Example 4 83±3.5 90±1.4 98±2.2 84.7% Comparison sample 32±0.5 49±4.3 58±3.1 55.2%
[0081] The test results in Table 1 and Table 2 show that: when the mass fractions are the same, the viscosity of Example 1, Example 3 and Example 4 in seawater or return water is greater than the viscosity of the comparative sample, wherein the viscosity ratio (η 2min / η 10min ), indicating the dissolution rate of the thickener particles; at the same time, the dissolution rates of the samples of Example 1, Example 3 and Example 4 in seawater or return water are faster than those of the control samples.
[0082] The above tests on the preferred embodiments show that the thickener polymer of the present invention can be quickly dissolved and significantly improve the temperature resistance and salt resistance of the thickener. Figure 1-2The Fourier infrared spectrum shows that the thickener polymer prepared by the present invention contains a large number of hydroxyl groups and ether bonds in its molecular structure. Furthermore, the hyperbranched polyether molecules with a three-dimensional spatial structure on the molecular chain of the thickener polymer of the present invention can not only expand the hydrodynamic volume of the copolymer molecules and increase the flow resistance of the molecular chain, but also form intermolecular hydrogen bonds and three-dimensional network structures with the carbonyl groups (C=O) of polyacrylamide or acrylic acid, further increasing the viscosity and suspended sand performance of the solution. In particular, in high-salt systems such as seawater and deep well return water, the non-ionic hyperbranched polyether covers the anion groups in the PAM molecular chain, shielding and protecting anions such as carboxylate (from polyacrylic acid) and sulfonate (from AMPS structural unit), preventing them from interacting with high-valent cations. Therefore, the thickener polymer of the present invention exhibits significant apparent viscosity in the return water solution at different mass concentrations.
[0083] At the same time, since the thickener polymer of the invention randomly introduces the hyperbranched polyether structure into the thickener molecular chain, the three-dimensional hyperbranched polyether can make the arrangement of the copolymer molecular chain looser, which is conducive to the diffusion and hydration of water molecules, so the above preferred embodiments all show a faster dissolution rate.
[0084] Moreover, the test data show that the introduction of AMPS and AHPEA units into the polymer molecular chain of the thickener of the present invention is beneficial to improving the salt resistance of the thickener. 7 g / mol, 2.37×10 7 g / mol, 3.15×10 7 g / mol), but their viscosity at different temperatures is related to the content of AHPEA. It is proved that hyperbranched polyether is beneficial to improve the salt resistance and viscosity increasing effect of thickener. In addition, according to Figure 3 As a result, the viscosity decrease rates of the four sample solutions of Example 1, Example 3, Example 4 and the comparative sample when heated from 80°C to 200°C were 39.7%, 42.8%, 40.1% and 60.3%, respectively, indicating that the introduction of the hyperbranched polyether structure helps the temperature resistance of the thickener solution.
[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A polymer for a high temperature resistant salt water based fracturing fluid thickener for oil and gas wells, characterized in that: The general structural formula of the polymer is as follows: The structural formula of Q is as follows: a, b, c, d are positive integers and a:b:c:d=45-70:17-35:7-15:5-10, and the viscosity average molecular weight of the polymer is 2.0×10 7 -3.8×10 7 g / mol.
2. A method for preparing a polymer for a high temperature resistant salt water based fracturing fluid thickener for oil and gas wells, characterized in that The steps are as follows: S1: dissolving acrylamide (AM), acrylic acid (AA), 2-acrylamido-2-methylpropyl sulfonic acid (AMPS), and acrylic acid monohyperbranched polyether alcohol ester in deionized water at a mass ratio of 46.5-64:17.5-28:7-15:10-20 to prepare a reaction solution, S2: then heating to 50-85° C. under nitrogen protection, adding an aqueous solution of a redox initiator and an aqueous solution of a water-soluble azo initiator to the reaction solution prepared in S1 at a constant rate to carry out a polymerization reaction for 3-8 hours, wherein the addition amount of the redox initiator and the water-soluble azo initiator is 0.15-0.45% of the mass of acrylamide (AM), respectively; S3: Then, a hydrolysis neutralizing agent is added to step S2 to adjust the pH value of the system to 7.0-7.3, and then the copolymer powder for thickening agent is obtained after freeze-drying, crushing and sieving.
3. The preparation method according to claim 2, characterized in that The redox initiator is at least one of a persulfate and a sulfite; wherein the persulfate is at least one of ammonium persulfate and potassium persulfate, and the sulfite is at least one of sodium sulfite and sodium bisulfite.
4. The preparation method according to claim 2, characterized in that The water-soluble azo initiator is at least one of azobiscyanovaleric acid, azobisisobutylimidazoline hydrochloride and azobisisopropylimidazoline.
5. The preparation method according to claim 2, characterized in that The mass percentage concentration of the aqueous solution of the redox initiator and the aqueous solution of the water-soluble azo initiator are both 5%.
6. The preparation method according to claim 2, characterized in that The hydrolysis neutralizing agent is sodium hydroxide.
7. The preparation method according to claim 2, characterized in that The copolymer has a particle size of not less than 120 meshes after being crushed and ground, and a water content of not more than 1.5%.
Citation Information
Patent Citations
Polyamide and amine hybridized nanosilicon dioxide hyperbranched polymer and preparation method thereof
CN103865008A
Water-soluble branched polymer as well as preparation method and application thereof
CN103910830A
PH stimulation response type intelligent hyperbranched scale inhibitor and application thereof
CN109836531A